Residents' breastfeeding knowledge, comfort, practices, and perceptions: results of the Breastfeeding Resident Education Study (BRESt) - Elizabeth Esselmont; Katherine Moreau; Mary Aglipay; Catherine M. Pound (BMC, 2018)
Abstract Background Physicians have a significant impact on new mothers' breastfeeding practices. However, physicians' breastfeeding knowledge is suboptimal. This knowledge deficit could be the result of limited breastfeeding education in residency. This study aimed to explore pediatric residents' breastfeeding knowledge, comfort level, clinical practices, and perceptions. It also investigated the level and type of education residents receive on breastfeeding and their preferences for improving it. Methods Descriptive, cross-sectional, self-reported online questionnaires were sent to all residents enrolled in a Canadian general pediatric residency program, as well as to their program directors. Resident questionnaires explored breastfeeding knowledge, comfort level, clinical practices, perceptions, educational experiences and educational preferences. Program director questionnaires collected data on current breastfeeding education in Canadian centers. For the resident survey, breastfeeding knowledge was calculated as the percent of correct responses. Demographic factors independently associated with overall knowledge score were identified by multiple linear regression. Descriptive statistics were used for the program director survey. Results Overall, 201 pediatric residents, and 14 program directors completed our surveys. Residents' mean overall breastfeeding knowledge score was 71% (95% CI: 69-79%). Only 4% (95% CI: 2-8%) of residents were very comfortable evaluating latch, teaching parents breastfeeding positioning, and addressing parents' questions regarding breastfeeding difficulties. Over a quarter had not observed a patient breastfeed. Nearly all agreed or strongly agreed that breastfeeding promotion is part of their role. Less than half reported receiving breastfeeding education during residency and almost all wanted more interactive breastfeeding education. According to pediatric program directors, most of the breastfeeding education residents receive is didactic. Less than a quarter of program directors felt that the amount of breastfeeding education provided was adequate. Conclusion Pediatric residents in Canada recognize that they play an important role in supporting breastfeeding. Most residents lack the knowledge and training to manage breastfeeding difficulties but are motivated to learn more about breastfeeding. Pediatric program directors recognize the lack of breastfeeding education.